PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN PATIN (Pangasius SP.) DI SISTEM RESIRKULASI DENGAN PADAT TEBAR BERBEDA - Annisa Septimesy; Dade Jubaedah; Ade Dwi Sasanti (Universitas Sriwijaya, 2016)
ABSTRACT The purpose of this study was to observe the effect of stocking density on the growth and survival of catfish (Pangasius sp.) 3 ± 0,5 cm in a recirculation system with water flow of 0.1 L.sec-. This study was conducted in May - June 2016 in the Basic Laboratory of Fisheries, University of Sriwijaya. The research method used a completely randomized design with three treatments and three replications. The treatment were stocking density of fish 20 ind.L-1 (P1),30 ind.L-1 (P2),and 40 ind.L-1 (P3). Parameters observed were fish growth, survival rate and water quality. The results showed that the different stocking density on a recirculation system with water flow 0.1 L.sec-1 did not significantly different to the survival rate. In this research P1 treatment with stocking density 20 fish.L-1was the best treatment, with absolute weight growth 1.03 ± 0.43 g, absolute length growth 1.86 ± 0.50 cm, and survival rate 73.34 ± 4.30 %. Keywords : Stocking density, Recirculation system, Pangasius sp.